2013
DOI: 10.1088/1748-9326/8/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

Water use for electricity in the United States: an analysis of reported and calculated water use information for 2008

Abstract: Water use by the electricity sector represents a significant portion of the United States water budget (41% of total freshwater withdrawals; 3% consumed). Sustainable management of water resources necessitates an accurate accounting of all water demands, including water use for generation of electricity. Since 1985, the Department of Energy (DOE) Energy Information Administration (EIA) has collected self-reported data on water consumption and withdrawals from individual power generators. These data represent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
130
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 5 publications
(16 reference statements)
0
130
0
Order By: Relevance
“…Consumption is defined as the amount of water taken from a reservoir but not returned to it due to forces such as evaporative loss while withdrawals are defined as the total amount of water taken from the source (Macknick et al 2012;Averyt et al 2013). …”
Section: Water Usagementioning
confidence: 99%
See 1 more Smart Citation
“…Consumption is defined as the amount of water taken from a reservoir but not returned to it due to forces such as evaporative loss while withdrawals are defined as the total amount of water taken from the source (Macknick et al 2012;Averyt et al 2013). …”
Section: Water Usagementioning
confidence: 99%
“…approximately 40% of freshwater withdrawals, (King et al 2008a) which is defined as the total amount of water that is removed from a source (Kenny et al 2009). Power plants also account for approximately 3% of total domestic water consumption (Averyt et al 2013), which is defined as the portion of water that is not returned to the source from which it was removed (King et al 2008a). Due to their critical need for cooling water, thermoelectric power plants are vulnerable to water shortages that can occur during drought. )…”
Section: Introductionmentioning
confidence: 99%
“…This issue provides perhaps the most comprehensive and integrated effort to assess the water implications of electric power generation in the U.S., both at the national level and also with a high enough level of spatial resolution to assess watershed-level impacts. This issue includes the following sets of analyses: (a) a review of water factors from the primary literature [23 ] and comparison of reported and calculated water use [22]; (b) description of a linked energy and water modeling framework (ReEDS and WEAP) [44]; (c) modeling of low carbon electricity futures [37], with assessment of the water impacts of those scenarios at the national and regional level [34 ]; and (d) linking the results of the electricity scenarios with models of regional water systems for the southeastern U.S. [31,43] and southwestern U.S. [32,42].…”
Section: Long-term System-level Trends In Water For Energymentioning
confidence: 99%
“…The Energy Information Administration (EIA) has collected information reported by power plant operators for water consumption and withdrawals since 1985. However, these data have often had important discrepancies and inconsistencies, particularly when compared to calculated values [22,30]. Recent efforts have focused on consolidating and comparing calculated operational water use factors by fuel, technology and cooling system [23 ,24].…”
Section: Introductionmentioning
confidence: 99%
“…They also reported solar photovoltaic and wind as the lowest water consuming energy technologies, and thermoelectricity as the highest water consuming type of energy. Averyt et al [28] evaluated the water withdrawal and consumptive use of power plants in the U.S. (including ocean and fresh water) and observed a substantial difference between the obtained results and EIA estimations, mostly due to imperfect assumptions and misreported information regarding power plants.…”
Section: Introductionmentioning
confidence: 99%